(untitled) (Heritage, 2023)
The program of the teaching area of fine arts and culture, through which knowledge about visual arts in formal general education is acquired in the countries of Southeast Europe, is randomly positioned in the topics of traditional heritage, taught in an established way and placed in the environment of art history, at the transition of modern and postmodern and practical art work. Artistic tendencies realized in new media are difficult to introduce into the teaching process, because the interpretations are still in the discourse of fine arts and culture. In order to understand and follow contemporary visual practice, it is necessary to establish new paradigms in teaching about art, which requires redesigning and modernisation of the programs and the educational sector. The presentation of new media artistic practices and the use of digital technologies in teaching, as well as an interactive teaching approach where the screen image encourages the student to actively participate in the research process, are part of the novelties that are pointed out in this article, which should modernize and improve the teaching of art.